Quote-and-Reply in WeChat: A Conversation Analytic Study - Yajing Yang (Studies in Applied Linguistics & TESOL, 2025)
This study explores uses of the quote-and-reply (Q&R) function in WeChat through conversation analysis. Analyzing 7 naturally occurring chat samples, the research identifies 3 primary interactional practices: sequence-jumping, which enables responses to non-adjacent turns across temporal gaps; response facilitation, where quotes are incorporated in the message to enhance clarity and thematic coherence; and spotlighting prior text, which emphasizes specific messages for alignment or humor. Findings reveal how Q&R transforms digital communication by mitigating challenges of multi-party chats and asynchronous interactions. The study contributes to understanding how platform-specific features reshape conversation structures, offering insights for designing more effective digital communication tools.